Physical layer rateless codes for the SATCOM on‐the‐move system with blockage. (1st September 2020) - Dai, Jingke; Zhao, Peng; Zhang, Fenggan; Chen, Xiao
Summary: Physical layer rateless codes are employed to mitigate the link‐blockage in satellite communication on‐the‐move (SOTM) systems. Both nonsystematic raptor (NR) codes and systematic raptor (SR) codes are investigated, where the blockage‐channel is modelled as an additive white Gaussian noise‐contaminated binary erasure channel (AWGN‐BEC). The asymptotic performance of NR codes is obtained by extrinsic information transfer (EXIT) method, and it is proved theoretically that NR codes have capacity‐approaching performance on this channel. A modified EXIT method is proposed to analyze the asymptotic performance of SR codes since the channel outputs not only continuous message but also discrete message. Due to the poor performance of existing SR codes on blockage‐channels, the degree distributions are optimized and the resulting codes show much better performance. Moreover, the raptor codes are compared with hybrid automatic repeat request (HARQ) schemes in satellite communication systems. Abstract : The asymptotic performance of nonsystematic raptor (NR) codes are analyzed by extrinsic information transfer (EXIT) method, which are proved to have excellent performance on the blockage‐channels of satellite communication on‐the‐move (SOTM) systems. A modified EXIT analysis is proposed to investigate systematic raptor (SR) codes since the blockage channels output messages with not only continuous density but also discrete density. Due to the poor performance of existing SR codes on blockage channels, the degree distributions of them are optimized, which show much better performance.